2017
DOI: 10.1002/sctm.16-0427
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expansion of Skeletal Muscle Stem Cells from Bulk Muscle Cells in Soft Three-Dimensional Fibrin Gel

Abstract: Muscle stem cells (MuSCs) exhibit robust myogenic potential in vivo, thus providing a promising curative treatment for muscle disorders. Ex vivo expansion of adult MuSCs is highly desired to achieve a therapeutic cell dose because of their scarcity in limited muscle biopsies. Sorting of pure MuSCs is generally required for all the current culture systems. Here we developed a soft three‐dimensional (3D) salmon fibrin gel culture system that can selectively expand mouse MuSCs from bulk skeletal muscle preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…To restore the Dystrophin expression in skeletal and cardiac muscle is essential for relieving the muscle wasting and weakness as well as extending life span of the patients. In the current study, based on our recently established novel soft 3D salmon fibrin gel culture system, 22 which enables selectively expansion of MuSCs with highly reserved regenerative competency from a small amount of bulk skeletal muscle cells, we corrected disease-driving mutation directly in adult skeletal MuSCs from mdx mice using CRISPR/Cas9-based genome editing, followed by transplantation to restore Dystrophin protein expression in vivo in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To restore the Dystrophin expression in skeletal and cardiac muscle is essential for relieving the muscle wasting and weakness as well as extending life span of the patients. In the current study, based on our recently established novel soft 3D salmon fibrin gel culture system, 22 which enables selectively expansion of MuSCs with highly reserved regenerative competency from a small amount of bulk skeletal muscle cells, we corrected disease-driving mutation directly in adult skeletal MuSCs from mdx mice using CRISPR/Cas9-based genome editing, followed by transplantation to restore Dystrophin protein expression in vivo in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we established a soft three-dimensional (3D) salmon fibrin gel culture system by the reaction of fibrinogen and thrombin, and showed that this system selectively expanded adult mouse MuSCs from bulk skeletal muscle preparations without the need for prior cell sorting 22 . In this study, we performed selection and primary expansion of skeletal MuSCs in 3D soft fibrin gels, followed by customized genome editing through CRISPR/Cas9 technology, and secondary expansion to propagate the repaired MuSCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies with cell lines of other origins (e.g. neurons [ 54 ] and stem cells [ 55 , 56 ]) are needed to fully reveal the specific benefits of salmon fibrinogen-chitosan scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that CRISPR‐Gold has the great potential to correct DNA mutation back to the wild type sequence and to restore fully functional dystrophin, without the use of viruses [35]. Tissue stem cell‐based therapies hold great therapeutic potential for the treatment of DMD and other muscle disorders [36]. In a 2017 study, Zhu et al [37] described how a fibrin‐gel culture system can be used to selectively expand muscle stem cells isolated from mice skeletal muscle cells to develop a mouse model of DMD.…”
Section: Critique Of Gene Modification Strategies In Animal Models Anmentioning
confidence: 99%